SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN JASA PENGIRIMAN PADA PT HM SAMPOERNA DENGAN METODE SIMPLE ADDITIVE WEIGHTING - Rikiwanto sinaga; luthfia rohimah; Ani Yoraeni (SPECTA Journal of Technology, 2022)
Freight forwarder is a business partner for the company to deliver some goods to various regions in the world. The companies often face a few problems when delivering their product, such as inaccuracy of providing a delivery service by considering several factors like shipping prices, packaging of goods, time of delivery, delivery security, quality of logistic vehicles and other facilitations. This study developed a Decision Support System which used Simple Additive Weighting (SAW) method in order to obtain information on the best Freight Forwarder. It aims to help the companies to solve logistic problems and losses.  Based on the calculated data, Pt Selog scores 0.9185 which is the best of alternative freight forwarder. The second place is Pt Tanto scores  0.8675. Next, PT Puninar is 0.8615 and PT WASHENG is 0.796.